Hidden information in paintings that manifests itself in the near infrared spectrum : Skrivena informacija u slikarstvu koja se manifestira u bliskom infracrvenom spektru - Žiljak Vujić, Jana (Array, 2019)
For each pigment and dye, we associate information about their absorption of light in the near infrared spectrum (NIR) at 1000 nm. Generally, pigments red, yellow, cyan blue, orange, white and “drap” (sandy brown) do not absorb NIR light. The NIR camera does not distinguish, recognize or “see” them, so the NIR photo is white. Such colors are marked with the letter "V" (visual, VIS). The area of green pigments (in our language, “zeleno” = green) is very different considering the absorption properties of NIR radiation. Some green pigments strongly absorb NIR radiation, while some green pigments absorb very little. That is why we have introduced the acronym Z as numerical information on the absorption of NIR light for all colorants, with a range from zero to ten. Painters are trained to mix colors with respect to their Z values. Dual images are produced. The NIR camera separates the drawing, the image, depending on the amount of Z color. The painter succeeds in arranging the colors so discreetly that two images are taken in the same place, one of which is seen by the naked eye, while the other requires an NIR camera to be seen. The idea of a VIS / NIR painting is accepted with the realization that there are many video surveillance (NIR) cameras around us: on the streets, in restaurants, in banks, in public entrances and entrances to private houses in general. The NIR design is used on documents, diplomas and banknotes as a general security method in graphic technology